"Одна школа – два народи": шкільні плебісцити в освітній діяльності УНДО (20-30 рр. ХХ ст.) - Мосійчук, Т. (Краєзнавство, 2016)
Стаття висвітлює загальні умови й напрями освітньої діяльності керівної політичної партії Західної України 20-30-х рр. ХХ ст. – Українського національно-демократичного об'єднання
через участь в проведенні шкільних плебісцитів. Автором проаналізовано основні методи роботи партії під час проведення плебісцитових акцій, їх ефективність та наслідки. Основний акцент зроблений на об'єднанні зусиль націонал-демократів і громадськості в боротьбі з
утраквізацією українського шкільництва. Статья освещает общие условия и направления образовательной деятельности руководящей политической партии Западной Украины 20-30-х гг. ХХ ст. – Украинского национально-демократического объединения через участие в проведении школьных плебисцитов. Автором
проанализированы основные методы работы партии во время проведения плебесцитовых
акций, их эффективность и последствия. Основной акцент сделан на объединении усилий национал-демократов и общественности в борьбе из утраквизацией украинского образования. The article highlights general conditions and directions of educational activity for leading political
party of Western Ukraine 20-30th of ХХ century – the Ukrainian national-democratic association through
participating in realization of school plebiscites. Author analyses the basic methods of work of
party during realization of plebiscites actions, their efficiency and consequences. A basic accent is done
on combining effort of national democrats and public in a fight against bilingualness of ukrainian school.
In the atmosphere of national and cultural and socio-economic pressure a fight for rights for the
Ukrainian people was led by leading legal party of Western Ukraine - Ukrainian national-democratic
association (UNDO). One of key tasks of national democrats was protecting of ukrainian education
from governmental politics of denationalization. For this reason the local and central cells of party
participated actively in realization of school plebiscites.
Without regard to the ponderable contribution of party to cultural and educational development of
edge, basic attention of researchers attracted political and economic activity of UNDO. In ukrainian
historiography the outlined problem was episodically examined in scientific works of M. Kuhutiak,
I. Soliar, O. Potikha; in polish historiography – R. Tomchyk, R. Torzhetskyi, A. Khoinovskyi.